Malignant Fibrous Histiocytoma in a Pigeon - Amin Derakhshanfar; Mohammad Mehdi Oloumi (Iranian Journal of Veterinary Surgery, 2008)
Case Description- A pigeon with an abnormal mass on right wing was referred to the Veterinary Clinic of Shahid Bahonar University of Kerman. Treatment and Outcome- The mass was removed surgically and histopathologic examination was done. Microscopic findings revealed a stori-form pattern of atypical and pleomorphic spindle-shape tumor cells with histiocytes and too many thick wall capillaries. Some bizarre cells, giant cells and lymphocytes along with collagenous stroma were seen. According to characteristic histopathologic features malignant fibrous histiocytoma(MFH) was diagnosed. Clinical Relevance-  MFH originates from a primitive mesenchymal stem cell is most frequently seen in the dog. This is the first report of MFH in birds.